Relationship between Cutting Depth and Spindle Speed on Cutting Accuracy of Aluminum 6061 on the TU-3A Retrofit CNC Machine - Wijaya, Mohamad Eq Setya; Mashudi, Imam (Universitas Merdeka Malang, 2024)
In the Mechanical Engineering Laboratory of the State Polytechnic of Malang, CNC machines experience decreased performance caused by abrasion and wear on mechanical components such as spindles, bearings, and rails, as well as electronic damage, outdated hardware and software, and inadequate maintenance. This study aims to evaluate the effect of cutting parameters on the roundness of machining results. The results of data analysis show that the depth of cut has a significant effect on roundness, with an F value of 8.05 and a P value of 0.030, which means significant at the 0.05 level. In contrast, spindle speed does not have a significant impact on roundness, with a P value far above 0.05. In addition, the interaction between depth of cut and spindle speed does not show a significant effect on roundness, with an F value of 2.08 and a P value of 0.206.